High Order Nonlinear Numerical Schemes for Evolutionary PDEs Proceedings of the European Workshop HONOM 2013, Bordeaux, France, March 18-22, 2013 - Abgrall, Rémi; Beaugendre, Héloïse; Congedo, Pietro Marco; Dobrzynski, Cécile; Perrier, Vincent; Ricchiuto, Mario (Lecture Notes in Computational Science and Engineering, 2014)
This book collects papers presented during the European Workshop on High Order Nonlinear Numerical Methods for Evolutionary PDEs (HONOM 2013) that was held at INRIA Bordeaux Sud-Ouest, Talence, France in March, 2013. The central topic is high order methods for compressible fluid dynamics. In the workshop, and in this proceedings, greater emphasis is placed on the numerical than the theoretical aspects of this scientific field. The range of topics is broad, extending through algorithm design, accuracy, large scale computing, complex geometries, discontinuous Galerkin, finite element methods, Lagrangian hydrodynamics, finite difference methods and applications and uncertainty quantification. These techniques find practical applications in such fields as fluid mechanics, magnetohydrodynamics, nonlinear solid mechanics, and others for which genuinely nonlinear methods are needed.